Gravity Anomalies and Bedrock Relief in Mizuho Plateau - Abe, Y.; Yoshimura, A.; Naruse, R. (1978)
P(論文) Distributional maps of free-air and Bouguer anomalies of gravity are presented, compiled from the data obtained by the oversnow traverses during the period from 1969 to 1974 over Mizuho Plateau, East Antarctica. Considerably large positive free-air anomalies were found in the region between Syowa Station and Mizuho Camp, while large negative anomalies were found to the southwest of Sandercock Nunataks. The existence of a largescale bedrock rise is suggested in the former region, namely 43°-45°E in 69°45′S, whereas a large-scale subglacial trough in the latter, namely 48°-52°E in 69°30′S. The distribution of Bouguer anomaly also showed irregular patterns in these regions. The value of Bouguer anomaly decreases in general with the increase of the surface elevation at a rate of about-40 mgal per 1000m. departmental bulletin paper